2023
DOI: 10.1371/journal.pone.0283286
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for ecdysone response genes in regulating egg production in adult female Rhodnius prolixus

Abstract: Ecdysteroids control ovary growth and egg production through a complex gene hierarchy. In the female Rhodnius prolixus, a blood-gorging triatomine and the vector of Chagas disease, we have identified the ecdysone response genes in the ovary using transcriptomic data. We then quantified the expression of the ecdysone response gene transcripts (E75, E74, BR-C, HR3, HR4, and FTZ-F1) in several tissues, including the ovary, following a blood meal. These results confirm the presence of these transcripts in several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
2
2
0
Order By: Relevance
“…Thirdly, knockdown of either EcR or usp significantly repressed oviposition in both H. vigintioctopunctata (Figures 2 and 3) and L. decemlineata (Figure 5) females. In accordance with our data, knockdown of EcR, usp, E75, E74 or FTZ-F1 decreases mature eggs, and severely reduces the laid eggs and their hatching rate in R. prolixus [23,24]. The reduced oviposition in 20E signal repressed females has also been documented in T. castaneum [7], D. melanogaster [25], Nilaparvata lugens [26,27], and Cimex lectularius [28].…”
Section: E Signal Triggers Choriogenesissupporting
confidence: 91%
See 3 more Smart Citations
“…Thirdly, knockdown of either EcR or usp significantly repressed oviposition in both H. vigintioctopunctata (Figures 2 and 3) and L. decemlineata (Figure 5) females. In accordance with our data, knockdown of EcR, usp, E75, E74 or FTZ-F1 decreases mature eggs, and severely reduces the laid eggs and their hatching rate in R. prolixus [23,24]. The reduced oviposition in 20E signal repressed females has also been documented in T. castaneum [7], D. melanogaster [25], Nilaparvata lugens [26,27], and Cimex lectularius [28].…”
Section: E Signal Triggers Choriogenesissupporting
confidence: 91%
“…Secondly, our data showed that the EcR and usp transcripts were present in the ovaries in both H. vigintioctopunctata (Figures 1-3) and L. decemlineata (Figures 1 and 5) females, similar to those in R. prolixus [23,24].…”
Section: E Signal Triggers Choriogenesissupporting
confidence: 58%
See 2 more Smart Citations